2013
DOI: 10.1021/jp406166z
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Spectroscopic Study of the Conduction Band of K3:Anthracene and K3:Phenanthrene

Abstract: We study anthracene and phenanthrene doped with potassium using X-ray absorption spectroscopy and electronic structure calculations. In addition, a comparison of molecular orbital calculations and solid state density functional theory calculations are presented. We find that potassium-doping partially populates the LUMO level of anthrancene and phenanthrene and that both the measured and calculated electronic structures of the doped systems are quite different from that of the pristine molecular systems. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…This hole reduces the screening of the nuclear charge, which tends to pull the local unoccupied orbitals to lower energies . Explicitly calculating the effect of the core hole on the ground-state electronic structure is a challenging task, so herein we use crystal field (CF) theory to approximate the influence of the core hole. CF is a very well-known approximation for determining the electronic structure of ionic compounds, and although it has largely been supplanted by ligand field theory or tight-binding models it is an appropriate approximation for modeling the core hole effect on insulating materials .…”
mentioning
confidence: 99%
“…This hole reduces the screening of the nuclear charge, which tends to pull the local unoccupied orbitals to lower energies . Explicitly calculating the effect of the core hole on the ground-state electronic structure is a challenging task, so herein we use crystal field (CF) theory to approximate the influence of the core hole. CF is a very well-known approximation for determining the electronic structure of ionic compounds, and although it has largely been supplanted by ligand field theory or tight-binding models it is an appropriate approximation for modeling the core hole effect on insulating materials .…”
mentioning
confidence: 99%
“…It affords low electronic thermal conductance (<0.005 KB/h) with ignorable phononic thermal conductance that both enhance its thermoelectric efficiency [22]. The phenanthrene also shows a superconcutance when it is doped with alkali metals [23,24]. Therefore, in this paper, the phenanthrene was attached to two gold leads in para-para, para-meta, and meta-meta connectivities with one or two carbon atoms substituted with (linked to) nitrogen atom "dopant" (phenyl radical "side group").…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by the literature, many phenanthrene derivatives have been synthesized, and their photophysical and thermal properties including their electrochemistry have been intensively studied. These derivatives offer access to various organic devices such as organic light-emitting diodes (OLEDs) [11][12][13][14][15][16][17][18], solar cells [19][20][21], superconductors [22,23], etc. In an independent study, Zhang and co-workers reported the synthesis of phenanthro-imidazole 1 (Figure 1) and used it for OLEDs [24].…”
Section: Introductionmentioning
confidence: 99%